x+2x=6x

Simple and best practice solution for x+2x=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2x=6x equation:


Simplifying
x + 2x = 6x

Combine like terms: x + 2x = 3x
3x = 6x

Solving
3x = 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
3x + -6x = 6x + -6x

Combine like terms: 3x + -6x = -3x
-3x = 6x + -6x

Combine like terms: 6x + -6x = 0
-3x = 0

Divide each side by '-3'.
x = 0

Simplifying
x = 0

See similar equations:

| 5x+1+15= | | X^2+7x-150=0 | | 5x=3x^2-9 | | 4x=ax+b | | (11+X)=2(X+4) | | X^2+7x+50=0 | | 12s^2+s-6=0 | | 39-8n=-5+4(-3n+8) | | 770*(x)=20 | | x^2+y^2-10x+16=0 | | (X^2+5)=0 | | X*(x+10)=144 | | -x=0.5x-3 | | 0=75x^3+90x^2+27x | | 4x^3-9x^2-28x=0 | | (w-4)(w+6)= | | 3(x-3)+3(x-1)=3x+3 | | 0.6(9x+6)=0.7-(x-3) | | X(11+X)=2x(4+2) | | (10g^3j^8v^6)(11gj^8)=0 | | -15x=-5(5x+7) | | 6=5X/2 | | log(4)(3x-9)=3 | | (2x+4x+9)=(2x+9) | | -9/5x=18/5 | | -3+2x=12 | | -37+2n=n+7(7-6n) | | -3(-1.8+3)=2(-1.8) | | 4-9p+2p=o | | 14z=4 | | 4.3x+52.7=24.9-9.6x | | F(-12)=4x-12 |

Equations solver categories